AlGaN/GaN HEMT on a free-standing GaN substrate with record 85.2% power-added efficiency at 2.45 GHz - Toshihiro Ohki; Atsushi Yamada; Yuichi Minoura; Yusuke Kumazaki; Kenji Saito; Masaru Sato (Applied Physics Express)
An AlGaN/GaN high-electron-mobility transistor (HEMT) on a free-standing GaN substrate achieved impressive power-added and drain efficiencies of 85.2% and 89.0%, respectively, at 2.45 GHz. We improved the GaN channel quality by reducing the C concentration and eliminated the buffer leakage path by removing the residual Si at the substrate-epitaxial layer interface. These improvements, combined with the reduction in dislocation density and the elimination of the nucleation layer by using a free-standing GaN substrate, contributed to the enhanced efficiency. To the best of our knowledge, the achieved efficiency represents the highest reported for GaN-based discrete HEMTs in this frequency band.